A COMPARISON OF THE CLINICAL AND METABOLIC OUTCOMES OF METFORMIN ALONE VERSUS METFORMIN COMBINED WITH CALCIUM AND VITAMIN D IN WOMEN WITH POLYCYSTIC OVARY SYNDROME: A QUASI-EXPERIMENTAL STUDY - SANGEETHA V JOICE; ANANTHIN; LEKSHMINATHG; INDU PC (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objective: This study evaluates the clinical and endocrine effects of metformin alone versus metformin combined with calcium and Vitamin D in women with Polycystic Ovary Syndrome (PCOS). PCOS is associated with insulin resistance, hormonal imbalances, and metabolic dysfunction. Methods: A quasi-experimental interventional study was conducted on newly diagnosed PCOS women (18–45 years). Participants were divided into two groups: Group I received metformin (500 mg/day), calcium (1000 mg/day), and vitamin D (60,000 IU weekly) for 8 weeks. Group II received only metformin (500 mg/day) for 8 weeks. The study compared changes in homeostatic model assessment of insulin resistance, lipid profile, and clinical parameters from baseline to the end of treatment. Results: Vitamin D supplementation along with calcium and metformin significantly improved body mass index (BMI) (24.93±3.78–23.84±1.11, p<0.001), waist circumference (WC) (87.83±7.83 cm–81.50±3.04 cm, p=0.007), and fasting glucose (95.48±10.64 mg/dL–92.18±6.43 mg/dL, p<0.001). Total cholesterol decreased (p=0.030), and high-density lipoprotein increased (p=0.029). Menstrual regularity (51.7–65%), acne (50–5%), and hirsutism (38.3–0%) improved significantly. Conclusion: Vitamin D supplementation with calcium and metformin resulted in significant improvements in BMI, WC, glucose levels, lipid profile, menstrual regularity, acne, and hirsutism in women with PCOS. In contrast, metformin alone did not lead to notable metabolic benefits.